Assessing the risk perception of cost overrun through importance rating - Gunduz, Murat; Maki, Omar Liqaa (Technological and Economic Development of Economy, 2018)
Cost overrun in construction projects is a common issue affecting project performance. After a review of the literature, a list of 39 cost overrun attributes were gathered and presented in a survey. The survey was distributed online to construction professionals. 101 complete responses were received and analyzed by importance index, frequency index, cost index, frequency adjusted cost index, Spearman’s rank correlation, student’s t-test, risk assessment and factor analysis. The results of the survey revealed that the main causes of cost overrun in construction industry include inaccurate cost estimation, improper planning and scheduling, unrealistic contract duration and requirements, frequent changes to the scope of work, frequent design changes, inadequate labor/skill availability, inflation on costs of machinery, labor, material and transportation.